First Report of Leaf Spot Disease on White Chrysanthemum (Chrysanthemum morifolium) Caused by Epicoccum sorghinum in Korea - Sieun Kim; Jong-Hwan Shin; Ha-Kyoung Lee; Seong-Chan Lee; You-Kyoung Han (Research in Plant Disease, 2024)
In September 2023, a leaf spot disease occurred on chrysanthemum (Chrysanthemum morifolium) in Imsil-gun Agricultural Technology Center, Korea. A fungal species was isolated from the diseased plant and identified as an ascomycete Epicoccum sorghinum based on morphological characteristics and phylogenetic analyses using the sequences of the ITS, TUB2, and ACT genes. A pathogenicity test revealed that the isolate was the causal agent of leaf spot disease on chrysanthemum. This is the first report of leaf spot disease caused by E. sorghinum on chrysanthemum in Korea.